2016
DOI: 10.1021/acs.jmedchem.6b01470
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tumor-Activated Prodrug Strategy Targeting Ferrous Iron Is Effective in Multiple Preclinical Cancer Models

Abstract: Here we describe a new approach for tumor targeting in which augmented concentrations of Fe(II) in cancer cells and/or the tumor microenvironment triggers drug release from an Fe(II)-reactive prodrug conjugate. The 1,2,4-trioxolane scaffold developed to enable this approach can in principle be applied to a broad range of cancer therapeutics and is illustrated here with Fe(II)-targeted forms of a microtubule toxin and a duocarmycin-class DNA-alkylating agent. We show that the intrinsic reactivity/toxicity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“… 49 This reduction is consistent with studies on 1,2,4-trioxolanes and plakortin derivatives that suggest rapid reduction of the peroxide functionality. 34 , 35 , 49 , 50 Consistent with previous studies, artesunate ( 2 ) also decomposed after exposure to iron ( Supplementary Figure 11 ). 7 Inactive analogues 32 and 41 were only partially decomposed after iron exposure ( Supplementary Figure 11 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“… 49 This reduction is consistent with studies on 1,2,4-trioxolanes and plakortin derivatives that suggest rapid reduction of the peroxide functionality. 34 , 35 , 49 , 50 Consistent with previous studies, artesunate ( 2 ) also decomposed after exposure to iron ( Supplementary Figure 11 ). 7 Inactive analogues 32 and 41 were only partially decomposed after iron exposure ( Supplementary Figure 11 ).…”
Section: Resultssupporting
confidence: 89%
“…Thus, the activity of FINO 2 could be due to the reduced product, as observed for some other peroxide-based drugs. 34 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…Our design of ICL-1 involved caging D-luciferin with a 1,2,4-trioxolane scaffold (51) used previously for in vivo delivery of therapeutic payloads in an Fe 2+ -dependent manner (50,54). The excellent pharmacokinetic properties of these therapeutic conjugates suggested that ICL-1 would have suitable in vivo properties for the desired imaging applications.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, SGT-94 uses the same targeted system to deliver a modified form of the retinoblastoma tumor suppressor gene, RB94, and has recently completed phase I assessment (NCT01517464). Another fascinating drug delivery mechanism involves a pro-drug strategy via trioxolane conjugation that reacts with ferrous iron in the tumor microenvironment to activate drug release (228). It is hoped that these delivery strategies will circumvent systemic toxicity and preliminary results seem promising.…”
Section: Targeting Iron Metabolism and Regulatory Mechanismsmentioning
confidence: 99%